Celebrating the 85th Birth Anniversary of Indus Rizakovich Tagirov - A.A. Litvin; N.A. Fedorova (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper marks the 85th birth anniversary of Professor of Kazan University, Member of the Tatarstan Academy of Sciences Indus Rizakovich Tagirov, a brilliant and famous historian. The reflections of I.R. Tagirov’s colleagues and students from Samara, Ulyanovsk, and Kazan on his personality and life path are provided. They reveal I.R. Tagirov’s role as a researcher, politician, supervisor, educator, and a remarkable human being.